2012
DOI: 10.1167/iovs.12-9791
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Sex Differences in Presbyopia

Abstract: This suggests that increased association of presbyopia for women is not due to a physiologic difference in accommodation but rather due to other sex differences, such as tasks performed and viewing distances. Age-based correction nomograms for presbyopia should therefore consider these sex differences when prescribing add powers for near tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 32 publications
8
44
6
1
Order By: Relevance
“…According to the literature, the prevalence of presbyopia tends to be higher among females. In our study there was no statistical correlation between the degree of presbyopia and age or sex (12) .…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…According to the literature, the prevalence of presbyopia tends to be higher among females. In our study there was no statistical correlation between the degree of presbyopia and age or sex (12) .…”
Section: Discussioncontrasting
confidence: 83%
“…(12) In addition to age and sex, the literature reports other factors related to presbyopia (13) . For example, the condition has been related to cardiovascular factors, but without statistical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that gender is not a risk factor for correctable NVI among younger or older age groups. A recent meta–analysis 14 has suggested that although there may be a weak association between presbyopia and female sex, this is unlikely due to physiologic differences in accommodation because accommodative amplitude does not differ between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Presbyopia is an age-related physiological change in the eye which results in loss of ability to accommodate for near viewing, 1 and generally occurs between ages 40 and 45 years or earlier with a female preponderance.…”
Section: Introductionmentioning
confidence: 99%